In Vitro And In Silico Analysis Of Xylanase Produced By Bacillus Licheniformis (Applied Biological Research, 2011)
A potent strain of Bacillus licheniformis was isolated among the various  xylanolytic bacteria obtained from agricultural fields of Allahabad (India). The  strain produced xylanase in a broad temperature (40-70ºC) and pH (5-11) range  with optimum production at 50ºC (for 48 hr) and pH 7.0+0.2. The peak enzyme  activity was observed when the substrate was supplemented with xylose,  ammonium nitrate and tryptone. A single form xylanase with a low molecular  weight (42 kDa) was purified to 3.9-fold with 6.7% recovery rate. Further, the  homology modeling of xylanase produced by B. licheniformis was carried out  using a template (PDB ID = 1AXK) having sequence similarity of 90% with the  query sequence. The reliability of final model confirmed a 92.8% acceptability of  Ramachandran plot statistics when validated through PROCHECK and  VERIFY 3D. A similar pocket volume obtained from CastP and Pocket Finder  were 253 and 268 Å3, respectively. The molecular orientation scored the lowest  energy level (-6.24 kcal mol-1) suggesting maximum stability of docked complex.  The hydrogen bonding and hydrophobic interactions between ligand and active  site lining residues suggested their importance in the catalytic activity and hence  this xylanase could be used effectively in industrial applications.
Keywords: Bacillus licheniformis; docking; homology modelling; xylanase